Function Follows Form - Kristof Dascher (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Urban policy visibly molds city shape. This paper's interest is in how city shape (less visibly) molds urban policy. The paper finds: A sufficiently skewed city will look after its center. That is, the more skewed a city's shape towards the city periphery, the more likely an urban majority against any policy that could take away from the city center. This, when broadly interpreted, complements Sullivan's (1896) ''form follows function'' view prominent in architectural theory. Function (building uses) also follows form (building contours). Ultimately combining both views may help explain further how, and when, cities sprawl.
Keywords: R50; D78; R12; 330